Byzantine Period Rock-Cut Architecture in Thrace - Mısırlı, Arif (Journal of History Culture and Art Research, 2023)
Rock-cut churches can be found throughout the Byzantine Empire. In Anatolia, examples can be found in the regions of Cappadocia, Phrygia, Lycaonia, and Thrace. The aim of this study was to determine the current status of the rock-cut religious buildings from the Byzantine period on the borders of Kırklareli and Edirne in Thrace and to examine and classify the identified buildings in terms of their periods and ground plan features and to show the historical and architectural values of these buildings. During the work process, a literature search was carried out to compare areas where rock-cut buildings are common. Written sources and drawings of these buildings were examined and field observations and photographs were taken. A total of nine buildings, seven from Kırklareli and two from Edirne, were examined as part of the study. Floor plan typologies, roof construction systems and architectural elements of the buildings were evaluated. It was found that although the floor plans are mostly single-aisled, there are also three-aisled and triconch examples and the roof construction system is generally a barrel vault. By examining the similarities and differences between the artifacts in Thrace and other regions, the original characteristics of the rock-cut religious structures were evaluated. It is possible to trace the rock-cut architecture in Thrace from the early to the late Byzantine period.